(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The Digital Economy is an economic activity focused on digital and electronic technologies. This includes e-business and commerce, as well as the goods and services they produce. Essentially, this definition covers all business, cultural, economic and social transactions carried out on the Internet and through digital communication technologies. The following article is devoted to the study of digital economy and its development trends.